The life-cycle of pharmaceuticals in the environment - Peake, B. M.; Braund, Rhiannon; Tong, Alfred Y. C.; Tremblay, Louis A. (Woodhead Publishing series in biomedicine ;, 2016)
The Life-Cycle of Pharmaceuticals in the Environment identifies pathways of entry of pharmaceuticals into the environment, beginning with the role of global prescribing and disposal practices. The book then discusses typical levels of common pharmaceuticals and how they can be determined in natural waters such as raw and treated sewage, and in potable water. In addition, sections examine methods currently available to degrade pharmaceuticals in natural waters and some of their ecotoxicological impacts, along with future considerations and the growing concept of product stewardship. Encompasses the full lifecycle of common pharmaceuticals, from prescription and dispensing practices to their occurrence in a range of different types of natural waters and their environmental impact Explores the role of the healthcare system and its affect on users Beneficial for environmental engineers involved in the design and operation of appropriate degradation technologies of the pharmaceutical prescription and disposal practices.